Effectiveness of Using Braillpopal Media and Mosipedaly Media in Improving Toothbrushing Skill in The Visually Impaired - Elis Selvi Ryan Susanti; Silvia Prasetyowati; Siti Fitria Ulfah; Mohammad Hamiduzzaman (Forum Ilmiah Teknologi dan Ilmu Kesehatan (FORITIKES), 2024)
Health has a major impact on the quality of life of children, one of which is with children with disabilities such as blind children, which is a term for individuals who experience impairment in their vision, whether it is total blind (total blindness) or low vision (there is still some vision left). The visually impaired are slower to detect early symptoms of poor oral health. The use of BRAILLPOPAL (Braille Pop Up Dental) and MOSIPEDALY (Modified Panthom Dental Study) media is an effort to improve tooth brushing skills in the blind. Poor oral hygiene in blind students of SLB N 1 Bantul. To know the effectiveness of BRAILLPOPAL and MOSIPEDALY media in improving tooth brushing skills in the blind at SLB N 1 Bantul. Type of research Quasi Experiment with Pre-test and Post-test Design research design using total sampling with research subjects as many as 30 students. The study showed that there was a significant increase in tooth brushing skills in the blind after being given counseling with BRAILLPOPAL media and MOSIPEDALY media. The use of BRAILLPOPAL media is more effective than MOSIPEDALY media in improving tooth brushing skills in the blind at SLB N 1 Bantul with an average increase of 18.80. Conclusion: Education using BRAILLPOPAL media and MOSIPEDALY media shows that there is an effectiveness in improving tooth brushing skills in blind students of SLB N 1 Bantu.